Sensory Profile of Candied Tomatodates Using the Just About Right Method - Diapri, Syafian Putra; Jariyah, Jariyah; Priyanto, Anugerah Dany (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Candied tomato dates are processed candies made from tomatoes that are dried until they are shaped like dates. Sensory profiles are needed to obtain candied date tomatoes with the most optimal betel lime solution concentration treatment and blanching time based on penalty analysis methods (JAR and hedonic scales). This study used the just about right method combined with the hedonic scale (overall liking) in the treatment of candied date tomatoes with a concentration of betel lime solution (2%, 3% and 4% (b/b)) and blanching time (5 minutes, 10 minutes and 15 minutes). There are 17 sensory attributes that will be tested through the assessment of the JAR scale and the hedonic scale (overall liking). The data obtained was then processed using XLSTAT 2024 software. Based on the results of the penalty analysis, it was shown that the most optimal candied date tomatoes were candied date tomatoes with a concentration treatment of 3% betel lime solution and a blanching time of 15 minutes where there were 14 insignificant test attributes or p-value?0.05. Meanwhile, there are only 3 sensory attributes that need to be optimized or p-value?0.05, namely juicy texture (p-value = 0.002), sweet taste (p-value = <0.0001) and fruity taste (p-value = 0.017).